Evolution of Ocean Temperature and Ice Volume Through the Mid-Pleistocene Climate Transition - Elderfield, H.; Ferretti, P.; Greaves, M.; Crowhurst, S. J.; McCave, I. N.; Hodell, D.; Piotrowski A. M. (Science, 2012)
Earth's climate underwent a fundamental change between 1250 and 700 thousand years ago, the mid-Pleistocene transition (MPT), when the dominant periodicity of climate cycles changed from 41 thousand to 100 thousand years in the absence of substantial change in orbital forcing. Over this time, an increase occurred in the amplitude of change of deep-ocean foraminiferal oxygen isotopic ratios, traditionally interpreted as defining the main rhythm of ice ages although containing large effects of changes in deep-ocean temperature. We have separated the effects of decreasing temperature and increasing global ice volume on oxygen isotope ratios. Our results suggest that the MPT was initiated by an abrupt increase in Antarctic ice volume 900 thousand years ago. We see no evidence of a pattern of gradual cooling, but near-freezing temperatures occur at every glacial maximum.